Dari Metrik Volume ke Owned Media: Studi pada Dokumenter-Konseptual Digital Public Relations IKEA Indonesia dalam Perspektif Volume Trap - Ridha Handayani; Andhini Winariyanti; Mulharnetti Syas (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Digital transformation has shifted public relations (PR) from a message dissemination function to a strategic practice that requires organizations to continuously listen to, understand, and respond to their publics. This article aims to examine IKEA Indonesia’s digital public relations practices through a documentary-conceptual case study to understand the risk of the volume trap, namely the tendency to treat the amount of content, exposure, impressions, search volume, or website traffic as the ultimate evidence of reputational success. The study employs Digital PR Theory and Excellence Theory, using a qualitative approach and descriptive analysis of secondary data, including the Indonesia Top Digital Public Relations Award 2026, INFOBRAND.ID publications, media coverage, and IKEA Indonesia’s Bonding Instruction campaign. The analysis applies documentary thematic coding to digital visibility, indicative public responses, digital awareness, relational storytelling, owned media traffic, and feedback loop indicators. The findings indicate an emerging shift in public attention toward owned media, as reflected in the high number of website visitors. However, the interpretation remains limited due to the lack of data on traffic sources, the composition of organic and paid traffic, visit duration, returning users, and independently verified sentiment. This article proposes the Data-Based Dialogic Digital PR Planning Heuristic Framework as an evaluative guide to distinguish visibility metrics from reputational impact in digital PR evaluation.